EDUKASI KESEHATAN MELALUI PEMERIKSAAN ASAM URAT PADA MASYARAKAT DESA BONTOTANGNGA KECAMATAN BONTOTIRO KABUPATEN BULUKUMBA - wati, Rahma; Nurhidayat, Nurhidayat; Noviponiharwani, Noviponiharwani (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2023)
Uric acid is the end product of natural metabolic processes in the body. Usually, this disease can interfere with the sufferer's daily activities. Gout is a disease caused by the buildup of urate crystals in the tissues, especially in the joints. Detection of uric acid levels can be done using the stick method using the Nesco Multicheck tool. Gout examination activities can help mobilize the people of Bontotangnga Village to come to the Village Hall. The aim of Community Service in uric acid examination activities is so that the public knows the results of uric acid examinations and starts awareness to change lifestyles, especially if the results show abnormal values. This activity will be aimed at 45 people in the Bontotangnga Village area. From the activities that have been carried out, the results obtained are that of the 46 participants, 40% were in normal conditions and 60% were at high levels. Through this examination activity, people have a higher awareness of being able to maintain and improve their health, one way is by improving their diet.